Scrutinizing the Legal Consequences of Enforcing Data Privacy Protection Mechanisms as a Means of Enforcing the Competition Act, 2023 - Henry Raymond Kalungi (Uganda Christian University, 2024)
This dissertation examines the potential legal consequences of using data privacy protection mechanisms for competition law enforcement in Uganda. While both data privacy and competition law aim to create a fair and efficient marketplace, their goals and tools often diverge. This work analyzes the potential benefits and drawbacks of this approach, exploring the legal implications of enforcing the Competition act with the aid of personal data protection mechanisms. It examines relevant case law and legal frameworks to assess the viability and potential conflicts of personal data protection and privacy as a tool to enforce the Competition act,2023.